New sources of potato resistance to Phytophthora infestans at the diploid level - Jakuczun, Henryka; Wasilewicz-Flis, Iwona (Plant Breeding and Seed Science, 2004)
New sources of Phytophthora infestans (late blight) resistance are studied in two groups of diploids: complex Solanum hybrids and clones of pure wild Solanum species. In more advanced studies complex hybrids of Solanum verrucosum, S. phureja and S. microdontum were involved, which were intercrossed in various combinations. In this group, clones with resistance both in leaflets and tubers have been selected. In addition, highly resistant to late blight hybrids are outstanding in chosen quality traits. Resistance to P. infestans identified in the advanced hybrids has been successfully transferred into 4x level with various extent. The second group of sources recently included in research covers about 110 clones of five wild Solanum species (S. berthaultii, S. kurtzianum, S. michoacanum, S. ruiz-ceballozii and S. pinnatisectum). In 1999-2003 preselection of leaflets and tuber resistant clones was performed. Selected clones have been simultaneously characterized for male fertility and big pollen grains (2n) formation.